Computing and intelligent systems International Conference, ICCIC 2011, Wuhan, China, September 17-18, 2011, Proceedings, Part III - Wu, Yanwen (Communications in computer and information science, 2011)
This six-volume-set (CCIS 231, 232, 233, 234, 235, 236) constitutes the refereed proceedings of the International Conference on Computing, Information and Control, ICCIC 2011, held in Wuhan, China, in September 2011. The papers are organized in two volumes on Innovative Computing and Information (CCIS 231 and 232), two volumes on Computing and Intelligent Systems (CCIS 233 and 234), and in two volumes on Information and Management Engineering (CCIS 235 and 236).